Дослідження термічних і трибологічних властивостей вуглепластика на основі фенілону С-2 - Чигвінцева, Ольга Павлівна; Chigvintseva, Olga; Рула, Ірина Василівна; Rula, Iryna; Бойко, Юлія Володимирівна; Boyko, Yulіya (Луцький національний технічний університет, 2023)
Досліджені основні термічні і трибологічні властивості вуглепластика на основі ароматичного поліаміду фенілон С-2, армованого металвмісним вуглецевим волокном. Показано, що армування поліамідного в’яжучого хром-вмісним вуглецевим волокном у кількості 17 мас. % підвищує його термостійкість, знижує коефіцієнт тертя та збільшує зносостійкість і критерій працездатності матеріалу. The main thermal and tribological properties of carbon fiber reinforced plastic based on aromatic polyamide phenylon C-2 reinforced with metal-containing carbon fiber have been researched. It is shown that the reinforcement of the polyamide binder with chromium-containing carbon fiber in the amount of 17 wt. % increases the thermal stability of the polymer by an average of 25-35°С. The study of the possible mechanism and the calculation of the kinetic parameters of the process of thermal destruction of the developed carbon fiber indicates that it is best described by the equation of one-dimensional diffusion. At all studied sliding speeds, the coefficient of friction of carbon fiber decreased with an increase in specific loads by 1.7-2.3 times, and the wear resistance of the material increased being in the range of 5.0-3.5 · 10-9. The performance criterion PV of carbon fiber was 1.2 MPa · m/s, which was 1.5 times higher than the criterion PV of phenylone C-2. The developed carbon fiber is recommended as an antifriction material for friction units of machines and mechanisms.
Research of thermal and tribological properties сarbon plastic based on phenylone С-2
https://orcid.org/0000-0002-9091-7482 (Чигвінцева О. П.) https://orcid.org/0000-0003-4229-6463 (Рула І. В.) https://orcid.org/0000-0003-2850-0173 (Бойко Ю. В.)
Keywords: ароматичний поліамід фенілон С-2; aromatic polyamide phenylone С-2; хром-вмісне вуглецеве волокно; chromium-containing carbon fiber; вуглепластик; carbon plastic; термостійкість; thermal stability; коефіцієнт тертя; coefficient of friction; інтенсивність лінійного зношування; intensity of linear wear; критерій працездатності; performance criterion